ANALISIS REGULASI DIRI DENGAN PRESTASI BELAJAR SISWA KELAS IV SEKOLAH DASAR - Rosmalah Rosmalah; Makmur Nurdin; Aliah Asdilah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This type of research is a qualitative descriptive approach, which aims to determine self-regulation with the learning achievement of fourth grade students of UPTD SDN 236 Taletting. Data collection, observation and interviews. Data analysis techniques, data reduction, data presentation stage, drawing conclusions. The purpose of the research is to provide insight for further researchers, to become a teaching tool to know students' self-regulation. The results showed that students had good self-regulation. The conclusion of this study, self-regulation. indicators are independence, have self-confidence, behave in a disciplined manner, have a sense of responsibility, behave on their own initiative, control learning activities. Factors that affect learning achievement, physical health, motivation, school physical environment, class social environment. Student self-regulation is good because it meets indicators that affect regulation, while student achievement in grade IV UPTD SDN 236 Taletting is good because students have met the requirements (Minimum Graduation Criteria).